Morphological Characters of Plant Species of the Zingiberaceae Tribe in Joben Resort Gunung Rinjani National Park, East Lombok - Erika Wulan Milenia; Tri Mulyaningsih; Sukiman (Quagga: Jurnal Pendidikan dan Biologi, 2024)
Zingiberaceae is a family of aromatic herbaceous plants, pseudostem, and rhizomes. Members of this species are found in the low-high lands (2000 meters above sea level), in areas with very high rainfall, and in humid places. Resort Joben is located in the south of Mount Rinjani so the water source is quite abundant and the humid forest conditions are a place to grow various species of Zingiberaceae. This study aims to determine the species and distribution of Zingiberaceae in the Joben Resort, Rinjani Mount National Park, East Lombok. Sampling used the cruising method with five cruising lines, each line has a wide range of 20 meters.    Morphological characters identify using the reference book Vascular Plant Systematics, and the kinship relationship dendrogram was created using past 4.09 software. Samples were collected and documented as herbarium, then identified their morphological characters and species. The results of the study found six species of Zingiberaceae which belong to three sub-family, namely Zingiberoideae: Curcuma zanthorrhiza and Hedychium coronarium; Alpinioideae: Amomum dealbatum, Etlingera spinulosa and Etlingera rubroloba, and Costoideae: Costus spiralis.